2019
DOI: 10.1103/physrevb.99.014426
|View full text |Cite
|
Sign up to set email alerts
|

Correlation effects on ground-state properties of ternary Heusler alloys: First-principles study

Abstract: The strongly constrained and appropriately normed (SCAN) semi-local functional for exchangecorrelation is deployed to study the ground-state properties of ternary Heusler alloys transforming martensitically. The calculations are performed for ferromagnetic, ferrimagnetic, and antiferromagnetic phases. Comparisons between SCAN and generalized gradient approximation (GGA) are discussed. We find that SCAN yields smaller lattice parameters and higher magnetic moments compared to the GGA corresponding values for bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 103 publications
2
19
1
Order By: Relevance
“…In this paper we focus on alloys relevant for magneto-caloric effects. A comprehensive study within SCAN for other ternary Heusler alloys have been recently reported by Buchelnikov et al [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we focus on alloys relevant for magneto-caloric effects. A comprehensive study within SCAN for other ternary Heusler alloys have been recently reported by Buchelnikov et al [6].…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the effect of on-site repulsion energy captured by SCAN, one can consider Heusler compounds for which GGA fails. In particular, the Heusler compounds Co 2 FeSi is a good example since GGA fails to produce a half metallic gap while DFT+U calculations [5] and recent SCAN results [6] reproduce this feature. Since SCAN results agree well the DFT+U, effective Hubbard terms U can be deduced from the SCAN band structure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding a materials design of new shape-memory materials, Zhang et al [ 45 ] demonstrated that the substitution of Cu for Sn in Ni-Mn-Sn alloy enhanced the magnetic-field-induced reverse martensitic transformation. Next, Buchelnikov et al [ 46 ] studied correlation effects in ground-state properties of Heusler alloys Ni-Mn-Ga and Ni-Mn-Ga-Sn comparing properties of ferro-/ferri- and antiferromagnetic phases. As another example, Benguerine et al [ 47 ] compared structural, elastic, electronic, and magnetic properties of Ni MnSb, Ni MnSn and Ni MnSb Sn magnetic shape memory alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Bungaro et al 26 performed both phonon dispersion and FS calculations demonstrating that GGA corrections to LSDA are beneficial in order to improve the agreement between theory and experiment. Since correlation effects in Ni 2 MnGa appear to play a crucial role on total energies, DOS, and magnetic moments 37,38 , we also expect major corrections beyond LSDA and GGA for describing FS nesting and phonon instabilities. A simple step forward is the strongly constrained and appropriately normed (SCAN) functional, which is the most promising meta-GGA scheme due to the number of exact constrains fulfilled by the exchangecorrelation energy [39][40][41] .…”
Section: Introductionmentioning
confidence: 99%